Colonic mucosal microbiome differs from stool microbiome in cirrhosis and hepatic encephalopathy and is linked to cognition and inflammation - Bajaj, Jasmohan S.; Hylemon, Phillip B.; Ridlon, Jason M.; Heuman, Douglas M.; Daita, Kalyani; White, Melanie B.; Monteith, Pamela; Noble, Nicole A.; Sikaroodi, Masoumeh; Gillevet, Patrick M. (American journal of physiology: Gastrointestinal and liver physiology, 2012)
Although hepatic encephalopathy (HE) is linked to the gut microbiota, stool microbiome analysis has not found differences between HE and no-HE patients. This study aimed to compare sigmoid mucosal microbiome of cirrhotic patients to controls, between HE vs. no-HE patients, and to study their linkage with cognition and inflammation. Sixty cirrhotic patients (36 HE and 24 no-HE) underwent cognitive testing, stool collection, cytokine (Th1, Th2, Th17, and innate immunity), and endotoxin analysis. Thirty-six patients (19 HE and 17 no-HE) and 17 age-matched controls underwent sigmoid biopsies. Multitag pyrosequencing (including autochthonous genera, i.e., Blautia, Roseburia, Fecalibacterium, Dorea) was performed on stool and mucosa. Stool and mucosal microbiome differences within/between groups and correlation network analyses were performed. Controls had significantly higher autochthonous and lower pathogenic genera compared with cirrhotic patients, especially HE patients. HE patients had worse MELD (model for end-stage liver disease) score and cognition and higher IL-6 and endotoxin than no-HE. Mucosal microbiota was different from stool within both HE/no-HE groups. Between HE/no-HE patients, there was no difference in stool microbiota but mucosal microbiome was different with lower Roseburia and higher Enterococcus, Veillonella, Megasphaera, and Burkholderia abundance in HE. On network analysis, autochthonous genera ( Blautia, Fecalibacterium, Roseburia, and Dorea) were associated with good cognition and decreased inflammation in both HE/no-HE, whereas genera overrepresented in HE ( Enterococcus, Megasphaera, and Burkholderia) were linked to poor cognition and inflammation. Sigmoid mucosal microbiome differs significantly from stool microbiome in cirrhosis. Cirrhotic, especially HE, patients' mucosal microbiota is significantly different from controls with a lack of potentially beneficial autochthonous and overgrowth of potentially pathogenic genera, which are associated with poor cognition and inflammation.